Wind and Solar Hybrid Energy Generation - Mohammed, Al-Asbahi Mahmoud Mustafa Yaseen; San, Low Yee (Journal of Applied Technology and Innovation, 2019)
The main aim of this project is to design and develop a hybrid wind and solar energy generation which can increase the electrical energy’s efficiency by using the wind turbine and solar panels. The implemented system aims at providing an amplified alternative source of renewable energy to cater for the already diminishing, pollutant and scarce traditional fuels such as oil, gas and coal. The implemented hybrid design consists of vertical axis wind turbine and two solar panels which are used to supplement the power generated especially during hot days when the wind speed is low. A permanent magnet synchronous generator redesigned from a recycled stepper motor and implemented with a total number of 9 copper wound coils for the stator and by using rare earth magnets for the rotor (shaft). The hybrid system implemented is able to generate maximum power of 75.05 W and minimum power of 18.2 W.